Advanced analysis of free visual exploration patterns in schizophrenia - Sprenger, Andreas; Friedrich, Monique; Nagel, Matthias; Schmidt, Christiane S.; Moritz, Steffen; Lencer, Rebekka (Frontiers in Psychology, 2013)
Background: Visual scanpath analyses provide important information about attention allocation and attention shifting during visual exploration of social situations. This study investigated whether patients with schizophrenia simply show restricted free visual exploration behaviour reflected by reduced saccade frequency and increased fixation duration or whether patients use qualitatively different exploration strategies than healthy controls. Methods: Scanpaths of 32 patients with schizophrenia and age-matched 33 healthy controls were assessed while participants freely explored six photos of daily life situations (20 seconds/photo) evaluated for cognitive complexity and emotional strain. Using fixation and saccade parameters, we compared temporal changes in exploration behaviour, cluster analyses, attentional landscapes and analyses of scanpath similarities between both groups. Results: We found fewer fixation clusters, longer fixation durations within a cluster, fewer changes between clusters, and a greater increase of fixation duration over time in patients compared to controls. Scanpath patterns and attentional landscapes in patients also differed significantly from those of controls. Generally, cognitive complexity and emotional strain had significant effects on visual exploration behaviour. This effect was similar in both groups as were physical properties of fixation locations. Conclusions: Longer attention allocation to a given feature in a scene and less attention shifts in patients suggest a more focal processing mode compared to a more ambient exploration strategy in controls. These visual exploration alterations were present in patients independently of cognitive complexity, emotional strain or physical properties of visual cues implying that they represent a rather general deficit. Despite this impairment, patients were able to adapt their scanning behaviour to changes in cognitive complexity and emotional strain similar to controls.